Women's rugby for all: Toward an intersectional women's rugby research agenda - Mkumbuzi, N. S. (European Journal of Sport Science, 2024)
Women rugby players are participating in the sport at the highest levels to date. However, despite this increase in participation, sports sciences and sports medicine/sports physiotherapy (SEMS) research output has not mirrored this increase. Females have hormonally mediated anatomical and physiological profiles, which may have implications for rugby performance, injury risk and rehabilitation outcomes. However, hormonal fluctuations and the physiological differences between the sexes are not the only contributors to sex-related differences in the rugby experience. Rugby is a highly gendered environment, which operates within a hegemonic masculine norm and marginalises female and women athletes. Further, while women players in general are underrepresented in sports sciences and SEMS research, women rugby players and experts from ethnic minorities and the Global South are near invisible in the literature as they are marginalised on multiple fronts. Sports sciences and SEMS research should take an intersectional lens to investigate the joint relationship between the various sources of inequity in rugby. Intersectional research in women rugby players would encourage the conceptualisation and analysis of the complex social inequalities that the most marginalised women players and those who simultaneously negotiate multiple identities experience. Such data can better inform federation-level interventions and policy changes to address the needs of historically marginalised player populations as our research portfolio will be more representative of the world's rugby population.